2020
DOI: 10.1186/s13063-019-3999-7
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture of fascia points to relieve hand spasm after stroke: a study protocol for a multicenter randomized controlled trial

Abstract: Background: The loss of functional ability of patients after stroke is mostly caused by dysfunction of the upper limbs, especially the hands. Hand functional exercise is the premise of alleviating hand dysfunction, and the relief of hand spasm is the basis of timely and effective hand functional exercise. Previous clinical observation have shown that fascial-point needling can effectively alleviate hand spasm immediately after stroke, but further evidence from large-sample studies is needed. The overall object… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…By the end of the acute stroke period, hemiparesis was observed in 81.2 % of patients who survived, including hemiplegia -11.2 %, severe and rough hemiparesis -11.1 %, mild and moderate hemiparesis -58.9 %. The indicators do not differ from data of other studies [3,4,7,9].…”
Section: Materials and Methods Of Researchcontrasting
confidence: 43%
“…By the end of the acute stroke period, hemiparesis was observed in 81.2 % of patients who survived, including hemiplegia -11.2 %, severe and rough hemiparesis -11.1 %, mild and moderate hemiparesis -58.9 %. The indicators do not differ from data of other studies [3,4,7,9].…”
Section: Materials and Methods Of Researchcontrasting
confidence: 43%
“…In the real world, acupuncture treatment enhances function of stroke patients better than conventional drug treatment. The study by Liu and others found that for patients with flaccid paralysis, the combination of the major meridian method combined with staged acupuncture has a more remarkable effect and effectively enhanced the patient's FMA score and daily living ability [ 29 ]. Song and others pointed out that, whether it is cerebral infarction or cerebral hemorrhage, the combined therapy of scalp acupuncture and body acupuncture combined with Bobath therapy can improve their neurological deficit and limb mobility and relieve muscle spasm [ 30 ].…”
Section: Discussionmentioning
confidence: 99%